SCHOOL HEALTH: THE TEACHER CONCEPTION OF THE PUBLIC ELEMENTARY EDUCATION (1st THE 4 th) IN THE CITY DE JEQUIÉ-BA (Fiep Bulletin - online, 2015)
The health education is the basis for adoption and development of critical thoughts and favorable behaviors for maintenance of an ideal of healthful life. The elementary education professors have an important function inside this context for acting directly with children in process of intellectual formation and behavioral development.  Regarding this, the present study had the intention to investigate the conception of the elementary education teachers about the school health and to characterize the formation of these professionals about this thematic. A qualitative methodology was used, being the sample consisting of 42 professors of the education public net in the city of Jequié-BA.  The data had been collected through a half-structuralized questionnaire and later analyzed following the proposal of thematic analysis.  As results, it was observed that 61% of the professors had affirmed to have studied health contents, being that of these, 31.5% do not consider such satisfactory study.  With relation to the study of the National Curricular Parameters (NCP), 95.2% had access; however it related to the transversal health issue, 59.5% had told to have studied. Concerning the preparation of the professors to work with the transversal health issue, it was observed that 50% did not feel prepared due the lack of theoretical subsidies (61,9%) and the lack of resources (33,3%).  The found results excite the necessity of accomplishing a good formation process for the teaching and qualifications that involve the health thematic, which could be reached by the effectiveness of the health professional actions in the school environment.
Keywords: School Health; Education in Health; Teacher.